Does customer-base structure influence managerial risk-taking incentives? - Chen, Jie; Su, Xunhua; Tian, Xuan; Xu, Bin (Journal of Financial Economics, 2022)
We find strong evidence that when a firm's customer base is more concentrated, the firm's CEO receives more risk-taking incentives in her compensation package. This finding is robust to numerous alternative measures, alternative specifications, alternative subsamples, and different attempts that mitigate endogeneity concerns. Further, the positive effect of customer concentration on CEO risk-taking incentive provision is more prominent when the CEO is more reluctant to take risks, when the firm has more investment opportunities, and when the firm is more prone to the costs of losing large customers. These findings are consistent with the notion that boards provide additional risk-taking incentives to offset the CEO's aversion to the risk of non-diversified revenue streams, thereby preventing excessive managerial conservatism at the expense of value maximization.